Perjumpaan Injil dan Budaya Di Kepulauan Sabu-Raijua Pada Abad XIX & XX - Yuda D. Hawu Haba (Institut Agama Kristen negeri Kupang, 2021)
The encounter between the gospel and culture whenever and wherever in the history of the church can take place well or can be useful for both if there is dialogue, openness to give and receive one another. A temporary answer and as one of the hermeneutical tasks, namely the effort to find out in-depth not only the meaning of something but also the background and all the processes why people arrive at this understanding. This is not an easy job. The hermeneutic method towards the Bible (text) but also on culture (context). The encounter between the gospel and culture must be contextual so that it gives a very deep meaning to humans. However, it should be remembered that contextualization is not just a tool of evangelism or a strategy to evangelize so that people will become Christians. This writing is not only a memory but also hoped to be able to renew our souls and movements as members of the congregation, in general, is looking to the future and carrying out God's calling tasks during a dynamically moving world. Believe that the Spirit of God gives light so that we can read this article through the eyes of faith and knowledge.